STUDY ON FATIGUE LIFE OF THIN-WALL STRUCTURE FASTENERS OF AIRCRAFT - CHEN QunZhi; ZHOU ZhiQiang; ZHang Qiang; SUN YanPeng (Jixie qiangdu)
A typical example of the damage failure of the thin-wall structure fasteners on aircraft was enumerated. The failure characteristics and its harmfulness of the thin-wall structure fasteners on aircraft were analyzed briefly. According to the fasteners loose and fall off failure problem of one sided connection structure of the leading edge of the wing on a certain aircraft,three improved design methods were put forward. And these fasteners with and without improved were experimental comparison verifyed by the tension-tension fatigue and the vibration endurance test methods. The impact vibrationn test device was developed to simulation or representation the failure mode and failure course of fasteners during vibration fatigue loading. A vibration fatigue test method on the thin-wall structure fasteners on aircraft was initially established. The results showed that there is essential difference on failure mode,damage mechanism,wreck destroy break appearance and pattern distributions of fatigue life of the thin-wall structure fasteners between the classical fatigue loading and the vibration fatigue loading. Based on the test results,the preferred and alternative improved design methods on the fasteners of one sided connection structure of the leading edge of the wing on a certain aircraft were provided.